Rāingān kānsamrūat khō̧mūn phư̄nthān nai khēt Khrōngkān Phatthanā Chonnabot Lumnam Mǣ Klō̜ng Phō̜.Sō̜. 2517. - Khrōngkān Phatthanā Chonnabot Lumnam Mǣ Klō̜ng. (Krung Thēp : Khrōngkān Phatthanā Chonnabot Lumnam Mǣ Klō̜ng, 1976)
Result of the preliminary survey concerning the general living conditions of the rural population in the Mae Klong area, Thailand, before May 1974.
In Thai.
Cover title.
Errata slip inserted.
Keywords: Agriculture and state -- Thailand -- Mae Klong River Region; Rural development -- Thailand -- Mae Klong River Region; Rural development projects -- Thailand -- Mae Klong River Region; Rural families -- Thailand -- Mae Klong River Region; Village communities -- Thailand -- Mae Klong River Region; Social surveys -- Thailand -- Mae Klong River Region